Smart orthopedic implants: the future of personalized joint replacement and monitoring - Eskandar Kirolos (Гений oртопедии)
Introduction Smart orthopedic implants integrate advanced sensor technologies to revolutionize joint replacement and orthopedic care. These implants enable real-time monitoring of key parameters such as wear, load distribution, and infection indicators, facilitating early intervention and personalized treatment. This review aims to evaluate the current advancements, clinical applications, challenges, and future directions of smart orthopedic implants. Methods A systematic literature review was conducted following PRISMA guidelines, analyzing peer-reviewed studies published between February 2015 and January 2025. Sources were retrieved from PubMed, Scopus, Web of Science, and Google Scholar. Inclusion criteria focused on technological innovations, clinical applications, and regulatory considerations. Results & Discussion Technological advancements in materials, sensor integration, wireless communication, and artificial intelligence have optimized implant functionality. Smart implants enhance postoperative monitoring, predict implant wear, and personalize rehabilitation. Despite their benefits, challenges such as biocompatibility, data security, battery life, and regulatory approval hinder widespread adoption. Addressing these issues through interdisciplinary research is critical for future developments. Conclusion Smart orthopedic implants have the potential to transform musculoskeletal healthcare by enabling real-time patient monitoring and personalized treatment strategies. Continued innovation in materials, AI‑driven analytics, and regulatory frameworks will be crucial for overcoming current limitations and ensuring their widespread clinical adoption.